(untitled) - Clinton, Bill (New York, 2004)
The former president looks back on his life and career, discussing his youth and education, his early public service, his years as governor of Arkansas, and his accomplishments during two terms in the White House.
Keywords: English language,Ngôn ngữ Anh; Study and teaching,Học và dạy